2019
DOI: 10.1002/ps.5570
|View full text |Cite
|
Sign up to set email alerts
|

Degradation studies of dimethachlor in soils and water by UHPLC‐HRMS: putative elucidation of unknown metabolites

Abstract: BACKGROUND: The analytical control of the presence of dimethachlor and its metabolites in environmental samples, such as water and soils, is a main concern. Degradation of this pesticide has been evaluated in two types of soils and two different water conditions at two concentration levels. For that purpose, a new liquid chromatography-mass spectrometry method has been developed and putative identification of new metabolites has been performed. RESULTS: An analytical method based on ultra-high-performance liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In this study, the use of MassChemSite and WebChembase software is described for the first time as a tool for the analysis of forced degradation products. Previously, MassChemSite proved to be a valuable tool to assist late-stage functionalization (LSF) through C–H functionalization of a drug during the drug discovery process and in the elucidation of new plant metabolites. Indeed, as a case study, MassChemSite software was applied for the data processing of the forced degradation of lansoprazole (a proton-pump inhibitor used to treat stomach and intestinal ulcers, erosive esophagitis, and Zollinger–Ellison syndrome), monitored in the following experimental conditions: acidic hydrolysis, basic hydrolysis, neutral hydrolysis, and oxidation. Later, WebChembase was employed to perform the data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the use of MassChemSite and WebChembase software is described for the first time as a tool for the analysis of forced degradation products. Previously, MassChemSite proved to be a valuable tool to assist late-stage functionalization (LSF) through C–H functionalization of a drug during the drug discovery process and in the elucidation of new plant metabolites. Indeed, as a case study, MassChemSite software was applied for the data processing of the forced degradation of lansoprazole (a proton-pump inhibitor used to treat stomach and intestinal ulcers, erosive esophagitis, and Zollinger–Ellison syndrome), monitored in the following experimental conditions: acidic hydrolysis, basic hydrolysis, neutral hydrolysis, and oxidation. Later, WebChembase was employed to perform the data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The current European Union (EU) guidelines indicate that one plant metabolite (SYN 500003) of mandipropamid is more acutely toxic than mandipropamid (JMPR, 2008), but the confirmation of its metabolites in Chinese soil has not been documented. In addition, the identification of metabolites has often been delineated using radiolabeling (JMPR, 2008), liquid chromatography with mass spectrometry (LC-MS) (Gupta et al, 2012), and liquid chromatography with high-resolution mass spectrometry (LC-HRMS) (López-Ruiz et al, 2020). Among these techniques, LC-HRMS is the most accurate and reliable technique for the determination of a parent chemical and its metabolites because of its excellent identification capacity for known and unknown compounds (Coscollà et al, 2014;EFSA, 2012;Gómez-Pérez et al, 2014;López-Ruiz et al, 2017, 2020.…”
Section: Core Ideasmentioning
confidence: 99%
“…Among these techniques, LC-HRMS is the most accurate and reliable technique for the determination of a parent chemical and its metabolites because of its excellent identification capacity for known and unknown compounds (Coscollà et al, 2014;EFSA, 2012;Gómez-Pérez et al, 2014;López-Ruiz et al, 2017, 2020. For example, López-Ruiz et al (2020) not only monitored several known metabolites but also identified three new metabolites of dimethachlor in soil by ultra-high-performance liquid chromatography with highresolution mass spectrometry (UHPLC-HRMS). Therefore, the determination of metabolites of mandipropamid in Chinese soil using LC-HRMS is necessary.…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…The half-life of dimethachlor in soil is between 2 and 16 days 11 . However, in specific soil type and conditions half-life may be longer than 50 days 12 . Its effect on soil microorganisms is less studied in comparison with other chloroacetamide herbicides such as metolachlor or acetochlor.…”
Section: Introductionmentioning
confidence: 99%